2023
DOI: 10.1101/2023.03.24.533983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-linearity in motor unit velocity twitch dynamics: Implications for ultrafast ultrasound source separation

Abstract: Ultrasound (US) muscle image series can be used for peripheral human-machine interfacing based on global features, or even on the decomposition of US images into the contributions of individual motor units (MUs). With respect to state-of-the-art surface electromyography (sEMG), US provides higher spatial resolution and deeper penetration depth. However, the accuracy of current methods for direct US decomposition, even at low forces, is relatively poor. These methods are based on linear mathematical models of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Third, the BSS method can identify MUs at 30% MVC. This is the first study showing that MUs at 30% MVC can be identified using UUS, as previous studies have been constrained to very low force levels with single MU feedback (Lubel et al, 2022;Rohlén et al, 2020a) and from 2% up to 20% MVC (Carbonaro et al, 2022;Lubel et al, 2023). We expect declining performance at the higher force levels due to inherent non-linearities complicating the velocity field (Lubel et al, 2023) and violating the linear mixture assumption in both the BSS and STA methods.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Third, the BSS method can identify MUs at 30% MVC. This is the first study showing that MUs at 30% MVC can be identified using UUS, as previous studies have been constrained to very low force levels with single MU feedback (Lubel et al, 2022;Rohlén et al, 2020a) and from 2% up to 20% MVC (Carbonaro et al, 2022;Lubel et al, 2023). We expect declining performance at the higher force levels due to inherent non-linearities complicating the velocity field (Lubel et al, 2023) and violating the linear mixture assumption in both the BSS and STA methods.…”
Section: Discussionmentioning
confidence: 74%
“…This is the first study showing that MUs at 30% MVC can be identified using UUS, as previous studies have been constrained to very low force levels with single MU feedback (Lubel et al, 2022;Rohlén et al, 2020a) and from 2% up to 20% MVC (Carbonaro et al, 2022;Lubel et al, 2023). We expect declining performance at the higher force levels due to inherent non-linearities complicating the velocity field (Lubel et al, 2023) and violating the linear mixture assumption in both the BSS and STA methods. Going from a linear to a nonlinear BSS model (Hyvärinen et al, 2023b(Hyvärinen et al, , 2023a may possibly overcome this limitation by integrating prior velocity field information and, as discussed above, it is also important to estimate all the spikes accurately.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations